Lithium toxicity following Roux-en-Y gastric bypass: Mini review and illustrative case - Shahana Ayub, MD; Sundas Saboor, MD; Sadia Usmani, MD; Sana Javed, MD; Gauvain Kankeu Tonpouwo, MD; Saeed Ahmed, MD (American Association of Psychiatric Pharmacists, 2022)
Lithium is among the mainstays of treatment for bipolar disorder. Bariatric surgery can considerably change the oral bioavailability of drugs, particularly lithium. In this review, a 36-year-old male patient is described, who presented with lithium toxicity, including neurologic and gastric symptoms after undergoing Roux-en-Y gastric bypass. The mechanism of lithium toxicity is discussed; recommendations for clinicians regarding lithium use in postsurgical patients are provided; and previous case reports of lithium toxicity post-gastric bypass surgery are analyzed. Awareness and education of lithium absorption changes postbariatric surgery is essential for optimal patient care. Close clinical and drug concentration level monitoring is warranted.